- Strategi Pengembangan Sapi Perah LEISA Berkelanjutan di Kabupaten Kolaka Timur - Nur Santy Asminaya; Fuji Astuti Auza; Dian Agustina; Musram Abadi; Andi Murlina Tasse; Fahri Akbar (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to formulate a strategy for sustainable dairy cattle development using the LEISA (Low External Input Sustainable Agriculture) production approach in East Kolaka Regency, Southeast Sulawesi. The study was conducted in Lalolae and Ladongi Districts, which were purposively selected as dairy cattle development areas. Primary data were collected through interviews, observation, and documentation, while secondary data were obtained from relevant institutions. Data analysis used the IFE, EFE, IE, SWOT, and QSPM matrices. The results showed that the IFE (3.54) and EFE (3.70) values were in a strong internal position and a supportive external environment, placing the dairy cattle business in Quadrant I of the IE matrix. This position reflects a "growing and building" condition, thus requiring an intensive development strategy. The SWOT analysis produced several alternative strategies, while the QSPM results indicated that increasing production capacity and strengthening farmer institutions were the main priorities. Sustainable LEISA-based dairy cattle development in East Kolaka Regency can be achieved through optimizing local production resources, empowering institutions, and increasing collaboration between farmers, the government, and the private sector. It is concluded that the dairy farming sector in this region has high potential to be developed within an intensive and growth-oriented development framework.